Bison‐Fly: An open‐source UAV pipeline for plant breeding data collection. Issue 1 (31st July 2022) - Matias, Filipe Inácio; Green, Andrew; Lachowiec, Jennifer A; LeBauer, David; Feldman, Max
Abstract: Bison‐Fly is the open‐source pipeline of unoccupied aerial vehicle (UAV) applications for plant breeding developed by the Spring Wheat Breeding Program at North Dakota State University in partnership with the Drone2Phenome community. We present a step‐by‐step pipeline to collect, process, and apply UAV data for plant breeding to facilitate data processing, reduce errors, and create new traits. This open‐source R code can be easily adapted for different crops and improved according to user requirements. In addition, Bison‐Fly provides a free and complete dataset with (a) RGB, Multispectral, and Digital Surface Model orthomosaics from 15 time points throughout the season; (b) field trait data with experimental design; and (c) daily metadata with soil and weather information. We hope this pipeline helps guide students, researchers, and breeders on day‐to‐day activities. Bison‐Fly is available at https://github.com/filipematias23/Bison‐Fly . Core Ideas: An open‐source tutorial is offered for unoccupied aerial vehicle (UAV) applications on plant breeding using R language. An easy extraction of biological information from raster using field plot boundaries is provided. Bison‐Fly provides a robust and real field and UAV dataset from a wheat breeding program.